Audiology and Speech-Language Pathology Services in Pediatric Population During COVID Pandemic in Nepal - Bhatarai, Prabuddha; Bhattarai, Biraj; Karna, Sureshwor Lal (Nepalese Medical Journal, 2020)
The pandemic has affected the daily working of people worldwide, including Audiology and speech language services. The Audiology and speech-language pathology services require proximity to the patients and hence increases the risk for transmission of the virus. These services are required during this time are immense to utilize a critical period of language development. Teleservices are a suitable option to assess and rehabilitate the client at this time. In a country like Nepal, where limited professionals are working in this fi eld, telehealth not only reduces transmission risk but also could be useful for patients who cannot attend clinics regularly due to the unavailability of services near their reach. The Speech and Hearing Association and all professionals working in this field should be ready to accept the changes that will eventually lead to the growth of the fi eld and the reach of the services for the patients in need.